PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL PADA MATA PELAJARAN BAHASA INGGRIS KELAS IX SMP - Hashifah, Shafarina; Novrianti, Novrianti; Rayendra, Rayendra; Zen, Zelhendri (Journal of Mandalika Literature, 2023)
This study aims to develop digital comic media products for the English subject of class IX in junior high school, and to find out the process of developing learning media that is developed is feasible or not for use in the learning process by teachers and students. The type of research that is used in this research is research and development which is called by the terms iResearch and iDevelopment (R&D) using the iASSURE model. Ipadi this model is i6 i development stage i.e. stage I Analyze Learner, stage Set Standards and Objectives I (State Standards and Objectives), Stage I Select Media, Materials and Supporting Technology I (Select Media, Material and Technology), Stage I use Media, Material and Technology I (Utilize Media, Material and Technology), stage of Developing Student Participation (Require learner Participation) and I stage I Evaluation and Revision I (Evalute And Revise). iI-ivalidity test was performed on i3 iperson i.e. i2 imedia ivalidator and i1 immaterial ivalidator. The practicality test was carried out on 26 respondents i.e. students of class IIX C iSMP iDevelopment UNP. The results of the assessment by the two imedia i-validators obtained an average score of i4.93 which was categorized as "very invalid". iThe results of the ivalidation of the assessment of the immaterial ivalidator obtained an average i4.73 i which was categorized as "very invalid", while the ipracticality test results of iproducts i by the students i obtained an average i4.77 i which was categorized i "very practical". Based on the results of the validity and practicality assessment, it can be concluded that the media products used are suitable for use in learning.